A potenciális városok környezeti állapotának értékelése, minősítése - Oláh, Ferenc (Tér és Társadalom, 1996)
The purpose of a comprehensive research, survey was to carry out the evaluation, qualification and classification of the state of environment in 177 – preliminary selected – settlements, for the criterion of comparability, in a numeric way. We have to emphasise that the fmdings only inform us about the present state of the environment. In the basic data of some aspects of the survey, in some settlements changes can take place in the near future. As a consequence of this, the perception and position of the state of the environment in an individual settlement can be different from what they are like today. Focusing on the individual settlements and building on a database which is wider and more precise than the comprehensive evaluation applied in this survey, if necessary, the evaluation system can be further improved and the situation which it reflects can be more accurate.